A study on the fabrication of multi material 3D patterns using inkjet printing technology - Ibrahim, Mustaffa (2007)
I n addition to its application in media printing, inkiet printing IS becotning an increasingly attractive option for the distribution and patterning of materials for a wide variety of applications such as the fabrication of prototype for the manufacturing sectors. Recently' a rapid protol)'ping method for building parts layer-by-layer has led to interest in fabrication of protol)'pes with extra functionalil)' by inkjet printing. ;\ new system is expected which can produce assemblies composed of parts with more than one color or with more than one material. This study intends to utilize Java program to manipulate CAD design data and interface them \vith a modified commercial 357 -nozzle piezoelectric printer with experiments focusing on the drop positioning and arrangement required to fabricate a multi material 3D patterns. Functional fluid materials such as silver nanoparticle conducti\T ink was successfully printed using inkjet printing technology to directly write an electronic circuit. In order to study the parameters affecting drop formation of an inkjet printer, a single nozzle piezoelectric inkjet system was also dC\'eloped to study basic parameters such as \'oltage amplitude, firing frequency and fluid viscosity. The understanding of these parameters reactions gi\'es a broader \·iew on work in the fabrication of multi material 3D patters using inkjet printing technology.